Prophylactic Indomethacin Worsens Short-Term Respiratory Outcomes in Extremely Low-Birth-Weight Infants - Mondal, Tapas; Chaudhuri, Dipayan; Li, Brian; Shivananda, Sandesh; Dutta, Sourabh (American Journal of Perinatology, 2014)
Objective To compare the effects of prophylactic indomethacin versus expectant management on short-term respiratory outcomes in extremely low-birth-weight (ELBW) infants.Methods This was a retrospective cohort study of ELBW infants with gestational age less than 28 weeks, born at a level III neonatal intensive care unit from 2004 to 2009. Patients were grouped based on whether they received prophylactic indomethacin or expectant treatment. The key outcome was the cumulative number of days of mechanical ventilation. Other outcomes were cumulative number of days supplemental oxygen and continuous positive airway pressure (CPAP) were required; duration of hospital stay; mortality; and other morbidities such as necrotizing enterocolitis and intraventricular hemorrhage. Multivariable linear regression was performed with treatment group and seven covariates, defined a priori, as predictor variables and cumulative number of days of mechanical ventilation as the outcome.Results There were 144 infants in the prophylaxis group and 221 infants in the expectant treatment group. At baseline, the Score for Neonatal Acute Physiology–Perinatal Extension, incidence of respiratory distress syndrome, and usage of antenatal corticosteroids were significantly higher in the prophylaxis group. The cumulative number of days of mechanical ventilation, supplemental oxygen, and CPAP were significantly higher in the prophylaxis group. On multivariable linear regression, after adjusting for confounders, use of prophylactic indomethacin (unstandardized β coefficient = 12.4; 95% confidence interval [CI]: 6.6, 18.1; p < 0.001), birth weight (β =  −0.025; 95% CI: −0.05, −0.001; p = 0.043), and gestation (β =  −4.5; 95% CI: −7.24, −1.8; p = 0.001) were the independent predictors of cumulative number of days of mechanical ventilation.Conclusion ELBW infants who received prophylactic indomethacin had significantly longer cumulative number of days of mechanical ventilation, supplemental oxygen, and CPAP. Prophylactic indomethacin is an independent predictor of cumulative number of days of mechanical ventilation.
Keywords: indomethacin prophylaxis; patent ductus arteriosus